Pengaruh Economic Value Added (EVA), Market Value Added (MVA), Financial Value Added (FVA) dan Cash Value Added (CVA) terhadap Harga Saham: Studi Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2021 - Tito, Tito Marta Sugema Dasuki; Sri Mulyani, Hani; Prihartini, Endah; Ismayati, iis (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
ABSTRACT The development of the banking world in Indonesia is very dynamic and modern. Shortly after the discovery of the initial case of corona in Indonesia in 2020, the giant bank sank with the JCI dropping by around 5% and there was a stop of around 30 minutes in trading. In general, stock prices decline, so an analysis of financial statements is carried out using a value added basis in the form of Economic Value Added (EVA), Market Value Added (MVA), Financial Value Added (FVA) and Cash Value Added (CVA). The purpose of this study is to determine the effect of EVA, MVA, FVA, and CVA partially and simultaneously on stock prices in banking companies listed on the IDX (Indonesian Stock Exchange) for the period 2019 to 2021. The sample of this research used purposive sampling technique. Based on the standards that have been obtained, there were around 18 banking companies during the three years of research so that 54 samples were obtained. Perform data analysis methods, panel data regression analysis and analysis of the coefficient of determination (R2) which previously carried out the classical assumption test using Eviews 9. Partially, this study shows that stock prices are not affected by EVA, FVA, and CVA, but are influenced by MVA. While stock prices are stated to be influenced simultaneously by EVA, MVA, FVA, and CVA. The results of the analysis of the coefficient of determination (R2) show that the explanation of the dependent variable on the contribution of all independent variables is around 66.58%, of which the remaining 33.42% is obtained from other variables.